“We Desire Everything Illustrating the History of Methodism That We Can Procure”: Examining the Methodist Collections at Drew University - Christopher J. Anderson (Theological Librarianship, 2012)
The Methodist Collections at Drew University (Madison, NJ) are among the largest and most influential anywhere. The present essay provides a thoroughly-documented overview of the genesis and ongoing development of these collections, from the mid-nineteenth century until the present. Particular attention is given to three major expansions (The George Osborn Collection, The Ezra Squire Tipple Collection, the incorporation of the General Commission on Archives and History Collection) which together have helped make the collections at Drew as important to researchers as they are today.